2014
DOI: 10.1080/14926156.2014.970906
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Ecological Knowledge in Science Education and Its Integration in Grades 7 and 8 Canadian Science Curriculum Documents

Abstract: Though science education has been prominent in the Canadian educational system, researchers increasingly recognize the scientific and educational value of integrating traditional ecological knowledge (TEK) into their curriculum. Despite national strategies to integrate TEK, Canada has yet to initiate a comprehensive study of its prevalence and representation within the curriculum. This study is the first to explore the current status of TEK in provincial Grade 7 and 8 science curricula and to make recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…As seen in Saskatchewan's successful case (Aikenhead & Elliot, 2010;Kim & Dionne, 2014;Saskatoon Public School Division, 2014), the meaningful integration of IK can be accomplished by consulting with local Aboriginal knowledge holders and experts. Instead of being used as a tool to tokenize IK, the contributions and knowledges of Aboriginal peoples can be introduced across all teaching strands and grade levels in a respectful manner towards Indigenous peoples without misrepresenting them as primitive or inferior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As seen in Saskatchewan's successful case (Aikenhead & Elliot, 2010;Kim & Dionne, 2014;Saskatoon Public School Division, 2014), the meaningful integration of IK can be accomplished by consulting with local Aboriginal knowledge holders and experts. Instead of being used as a tool to tokenize IK, the contributions and knowledges of Aboriginal peoples can be introduced across all teaching strands and grade levels in a respectful manner towards Indigenous peoples without misrepresenting them as primitive or inferior.…”
Section: Resultsmentioning
confidence: 99%
“…Kimmerer (2002) also pointed out that IK are unknowingly or knowingly ignored in curricula. Indeed, my previous study (Kim & Dionne, 2014) revealed that many Canadian jurisdictions showed either a lack of Indigenous-related content in their grades 7 and 8 science curricula (i.e., evidence of ignoring) and/or evidence of essentialism and appropriation of IK in their science curricula. However, unlike the other Canadian provinces and territories, Nunavut and Saskatchewan have made some headway in integrating IK into science curricula (Kim & Dionne, 2014).…”
Section: Current Status Of Ik In Canadian Science Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although preliminary, the research indicates a need for more effective and relevant mediation processes, tailored specifically, to Indigenous people. Secondly, the increasing number of studies on Indigenous knowledge in the fields of: environment (e.g., Kim & Dionne, 2014;Menzies & Butler, 2007;McGregor, 2004), health (e.g., Downey & Sweetwater, 2004;Milbur, 2004), education (e.g., Ball, 2004;Battiste & Henderson, 2009;Villegas, Neugebauer, Venegas, 2008) and Indigenous methodologies (e.g., Kovach, 2009;Tuhiwai Smith, 1999;Wilson, 2008), to name a few, demonstrate that Indigenous knowledge provides unique ways of interacting with, examining and understanding the world around us.…”
Section: Summarizing the Literaturementioning
confidence: 99%